Is SEEG safe? A systematic review and meta‐analysis of stereo‐electroencephalography–related complications. (21st February 2016) - Mullin, Jeffrey P.; Shriver, Michael; Alomar, Soha; Najm, Imad; Bulacio, Juan; Chauvel, Patrick; Gonzalez‐Martinez, Jorge
Summary: Objective: Stereo‐electroencephalography (SEEG) is a procedure performed for patients with intractable epilepsy in order to anatomically define the epileptogenic zone (EZ) and the possible related functional cortical areas. By avoiding the need for large craniotomies and due to its intrinsic precision placement features, SEEG may be associated with fewer complications. Nevertheless, intracerebral electrodes have gained a reputation of excessive invasiveness, with a "relatively high morbidity" associated with their placement. A systematic literature review and meta‐analysis of SEEG complications has not been previously performed. The goal of this study is to quantitatively review the incidence of various surgical complications associated with SEEG electrode implantation in the literature and to provide a summary estimate. This will allow physicians to accurately counsel their patients about the potential complications related to this method of extraoperative invasive monitoring. Methods: The systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA). We conducted MEDLINE, Scopus, and Web of Science database searches with the search algorithm. We analyzed complication rates using a fixed‐effects model with inverse variance weighting. Calculations for the meta‐analysis and construction of forest plots were completed using an established spreadsheet. The principal summary measures were the effect summary value and 95% confidence intervals (CIs). Results: The initial 1, 901 retrieved citations were reviewed. After removing 787 duplicates, the titles and abstracts of 1, 114 publications were screened. At this stage, studies that did not mention the absence or presence of complications following SEEG or that did not fulfill the inclusion criteria in any manner were excluded. After excluding 1, 057 citations, the full text was assessed in the resulting 57 articles for eligibility criteria. The most common complications were hemorrhagic (pooled prevalence 1.0%, 95% confidence interval [CI] 0.6–1.4%) or infectious (pooled prevalence 0.8%, 95% CI 0.3–1.2%). Five mortalities were identified (pooled prevalence 0.3%, 95% CI −0.1–0.6%). Overall, our analysis identified 121 surgical complications related to SEEG insertion and monitoring (pooled prevalence 1.3%, 95% CI 0.9–1.7%). Significance: This review represents a comprehensive estimation of the actual incidence of complications related to SEEG. We report a rate substantially lower than the complication rates reported for other methods of extraoperative invasive monitoring. These data should alleviate the concerns of some regarding the safety of the "stereotactic" method, allowing a better decision process among the different methods of invasive monitoring and ameliorating the fear associated with the placement of depth electrodes.